3. The Graphic Communication Actor: Generating Visual Rhetoric for Development Initiatives - Ebigbagha Sylvester Zifegha (Sciendo, 2020)
The art of using language for public expression in order to persuade target audience to support development initiatives is a key reason for graphic communication. This requires communication actors particularly, the graphic encoder to know salient input and output variables of communication for effective mediation. However, the prevalence ignorance of these variables, often results in ineffective media production that is counter-productive to development. Therefore, this paper focused on production of practical rhetoric in graphic language for development programmes. The paper employed the critical-historical-analytic examination and content analysis methods. It introduced the reader to the need for practical rhetoric in visual communication. Furthermore, it highlighted the salient input and output variables that the graphic communication actor need be conversant with in order to produce visual rhetoric, using the McGuire's Communication/persuasion Matrix. And it exemplified graphic media that result from application or neglect of the knowledge of the variables. The paper found that consideration of the variables afforded production of effective rhetoric in graphic language. The paper ended with the need for graphic encoders to internalize knowledge of the input and output variables and utilize it during the process of media production to generate visual rhetoric with desired effect.